2009
DOI: 10.3109/08860220903137517
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Caffeic Acid Phenethyl Ester on Cyclosporine A-Induced Nephrotoxicity in Rats

Abstract: CsA causes renal injury and CAPE prevents CAT- and lipid peroxidation-mediated nephrotoxicity via inhibition of oxidative process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 24 publications
1
18
1
Order By: Relevance
“…Several previous studies had suggested that cyclosporine nephrotoxicity may be improved or prevented by antioxidants. [12][13][14][15][16][17] A meta-analysis of clinical trials of CoQ10 for hypertension concluded that CoQ10 had potential for lowering blood pressure in hypertensive patients 18 ; however, in this study, no significant reduction of systolic blood pressure was observed when rCoQ10 was administered with cyclosporine. A possible explanation for this finding is that cyclosporine-induced hypertension may be caused by activation of the intrarenal renin-angiotensin axis, 7 but the renal protective effect of rCoQ10 may be accomplished by another mechanism.…”
Section: Discussioncontrasting
confidence: 60%
“…Several previous studies had suggested that cyclosporine nephrotoxicity may be improved or prevented by antioxidants. [12][13][14][15][16][17] A meta-analysis of clinical trials of CoQ10 for hypertension concluded that CoQ10 had potential for lowering blood pressure in hypertensive patients 18 ; however, in this study, no significant reduction of systolic blood pressure was observed when rCoQ10 was administered with cyclosporine. A possible explanation for this finding is that cyclosporine-induced hypertension may be caused by activation of the intrarenal renin-angiotensin axis, 7 but the renal protective effect of rCoQ10 may be accomplished by another mechanism.…”
Section: Discussioncontrasting
confidence: 60%
“…We cannot show that how CAPE alone affects the activities of antioxidant enzymes because it was not studied. On the other hand, we have shown previously that CAPE alone may directly increase CAT activity (37). Generally, CAPE does not affect GSH-Px activitiy in normal or injured animals.…”
Section: Discussionmentioning
confidence: 65%
“…RCoQ10 also diminished TGF-beta expression in the proximal renal tubular cells. There are several animal and clinical studies suggesting that antioxidative agents have some preventive effect of CyA nephrotoxicity (7)(8)(9)(10)(11)(12). In 2004, Dlugosz et al reported the benefit of CoQ10 on renal transplant recipients for the first time (13); however, they used ubiquinone, the oxidized form of CoQ10.…”
Section: Discussionmentioning
confidence: 99%